Self-managing team or tayloristic production chain? What can we learn from simulation-based work design trainings - Klonek, Florian; Parker, Sharon (2018)
Digitalisation, flexible job markets, new technologies and innovative forms of collaboration constitute increasing challenges for employers and the design of modern work. But how can we deal with these challenges and what do we know about the effect of good versus bad work design? Based on the job demands-resources model (JRM), we present a simulation-based training during which participants experience the effects of different work characteristics. We focus on the moderating effects of job control and job demands: The JRM assumes that job demands and job control interactively affect employee exhaustion and work engagement: Jobs with high control can buffer the strain-enhancing effect of job demands (buffer hypothesis) and increase work engagement (active learning hypothesis). We test these hypotheses in a workplace simulation during which participants have to produce ice-cream. Our results support the buffer hypothesis but not the active learning hypothesis. We discuss the added value of work design simulations for organisations, practitioners, and HR professionals.